Respiratory Influenza A Virus Infection Triggers Local and Systemic Natural Killer Cell Activation via Toll-Like Receptor 7 - Stegemann-Koniszewski, Sabine; Behrens, Sarah; Boehme, Julia D.; Hochnadel, Inga; Riese, Peggy; Guzmán, Carlos A.; Kröger, Andrea; Schreiber, Jens; Gunzer, Matthias; Bruder, Dunja (Frontiers in Immunology, 2018)
The innate immune system senses influenza A virus (IAV) through different pathogen-recognition receptors (PRR) including Toll-like receptor 7 (TLR7). Downstream of viral recognition natural killer (NK) cells are activated as part of the anti-IAV immune response. Despite the known decisive role of TLR7 for NK cell activation by therapeutic immuno-stimulatory RNAs, the contribution of TLR7 to the NK cell response following IAV infection has not been addressed. We have analyzed lung cytokine responses as well as the activation, interferon (IFN)-γ production and cytotoxicity of lung and splenic NK cells following sublethal respiratory IAV infection in wild-type (WT) and TLR7ko mice. Early airway IFN-γ levels as well as the induction of lung NK cell CD69 expression and IFN-γ production in response to IAV infection were significantly attenuated in TLR7-deficient hosts. Strikingly, respiratory IAV infection also primed splenic NK cells for IFN-γ production, degranulation and target cell lysis, all of which were fully dependent on TLR7. At the same time, lung type I IFN levels were significantly reduced in TLR7ko mice early following IAV infection, displaying a potential upstream mechanism of the attenuated NK cell activation observed. Taken together, our data clearly demonstrate a specific role for TLR7-signalling in local and systemic NK cell activation following respiratory IAV infection despite the presence of redundant innate IAV-recognition pathways.